Medical treatment for adenomyosis and/or adenomyoma - Kuan-Hao Tsui; Wen-Ling Lee; Chih-Yao Chen; Bor-Chin Sheu; Ming-Shyen Yen; Ting-Chang Chang; Peng-Hui Wang (Elsevier, 2014)
Uterine adenomyosis and/or adenomyoma is characterized by the presence of heterotopic endometrial glands and stroma within the myometrium, >2.5 mm in depth in the myometrium or more than one microscopic field at 10 times magnification from the endometrium-myometrium junction, and a variable degree of adjacent myometrial hyperplasia, causing globular and cystic enlargement of the myometrium, with some cysts filled with extravasated, hemolyzed red blood cells, and siderophages. Hysterectomy is a "gold standard" and definitive therapy for uterine adenomyosis, and many cases of adenomyosis have been diagnosed by pathological review retrospectively. As such, the diagnosis of adenomyosis is difficult, and this subsequently results in difficulty in the management of these patients, especially those who are symptomatic but have a strong desire to preserve their uterus. In our previous review, we found that the use of uterine-sparing surgery in the management of uterine adenomyosis and/or adenomyoma is still controversial, although some data support its feasibility. Conservative treatment is still needed in the group of patients that requires preservation of fertility and improvement of quality of life. However, studies focusing on the topic of medical treatment for adenomyosis are rare. In this article, current knowledge regarding the use of medical therapy for uterine adenomyosis, partly based on the understanding of endometriosis, is reviewed.